BRANDING HIPMI PEDULI JAWA TENGAH THROUGH STRATEGIC COMMUNICATION ACTIVITY - Selo Pangestu Imawan; Djoko Setyabudi; Agus Naryoso; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
This Final Assignment in the form of field work is based on a new organization underHIPMI Jawa Tengah, HIPMI Peduli Jawa Tengah. HIPMI Peduli Jawa Tengah is a neworganization that is not popular yet in HIPMI Jawa Tengah members, let alone in public.Through its branding activity, HIPMI Peduli Jawa Tengah can strengthen its HIPMI PeduliJawa Tengah brand.Because there’s a lot of HIPMI Jawa Tengah member who don't know about HIPMI PeduliJawa Tengah makes many HIPMI Peduli Jawa Tengah activities unknown to them and topublic. Based on persuasion theory, this work aims to entice members of HIPMI JawaTengah to know HIPMI Peduli Jawa Tengah activities better. Aside of that, this work alsoaims to increase the affection, cognition and behavior of the members and to persuadepeople to donate in HIPMI Peduli Jawa Tengah.On one month of execution in August, the event managed to increase awareness by 84%and donation by 34% of the members of HIPMI Peduli Jawa Tengah. This work also showsthat the branding activity done by HIPMI Peduli Jawa Tengah was successfully doneaccording to the goals that had been set beforehand.